การศึกษาพฤติกรรมการบริโภคและทัศนคติของผู้บริโภคสินค้าอินทรีย์ - สุขรัตน์, คณิต; อธินุวัฒน์, ดุสิต (Thai Journal of Science and Technology, 2019)
This study investigated the consumption behavior and attitude of organic products consumer by 400 samplings in Bangkok who had bought the organic products, with a questionnaire. Results revealed that most consumers have a good attitude towards organic products with 2-4 times/week buying the organic products for household consumptions. The most popular organic product items are fresh vegetables, fresh fruits, and rice. The consumer recognized that organic products are chemical free, good for health, and ecosystem friendly. However, their attitudes towards organic products are more expensive price than that of normal products. Organic product consumptions behavior hypothesis analysis revealed that the consumption factors, household planting objectives, and vegetable plant variety significantly (p = 0.05) affects consumer attitude and planting for household consumptions with 11.4 % (R2 = 0.114). This study indicates that grower should not set the price of organic products unfairly for encouraging consumers at all levels to access organic products easily. It has to increase public relations for recognition of organic products correctly and also to know the location of organic product market or green market nearby consumer’s home. This mention is organic product marketing strategy to support and promote consumer behavior and their attitude on organic products effectively.